FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN CATATAN ATAS LAPORAN KEUANGAN (CALK) OLEH PENGGUNA LAPORAN KEUANGAN PEMERINTAH (Studi Empiris pada Instansi Pemerintah di Jawa Tengah) - Tarina Rahmayani; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This study aims to examine the use of  Notes to The Financial Statements to the leaders, supervisory, or agencies in government for having a good decision function of government.to obtain the valid result, so this study using three variables independent such as, education, tenure, and socio culture. The population in this study was a government agency in Central Java. Samples were selected by using purposive sampling which the criteria was the leaders, supervisory, or agencies. The results showed that the variables of education, experience, socio culture affect significantly positive on the using of Notes to The Financial Statements.